2017
DOI: 10.1088/1361-6463/aa62d5
|View full text |Cite
|
Sign up to set email alerts
|

Continuously phase-modulated standing surface acoustic waves for separation of particles and cells in microfluidic channels containing multiple pressure nodes

Abstract: This paper describes continuously phase-modulated standing surface acoustic waves (CPM-SSAW) and its application for particle separation in multiple pressure nodes. A linear change of phase in CPM-SSAW applies a force to particles whose magnitude depends on their size and contrast factors. During continuous phase modulation, we demonstrate that particles with the target dimension are translated in the direction of moving pressure nodes, whereas smaller particles show oscillatory movements. The rate of phase mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…12d). When SSAW is combined with other techniques such as the frequency modulation using chirped IDTs 52 or the phase modulation 21 , it can be possible to arrange different types of microparticles or cells at distinct locations (Supplementary Fig. 13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12d). When SSAW is combined with other techniques such as the frequency modulation using chirped IDTs 52 or the phase modulation 21 , it can be possible to arrange different types of microparticles or cells at distinct locations (Supplementary Fig. 13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that pressure fields formed by standing surface acoustic waves (SSAWs) are capable of manipulating microparticles at a high resolution in a noninvasive manner 2126 . SSAW techniques also exhibit the potential to selectively manipulate various types of microparticles 21 , regulate cell–cell distances 22 , and engineer cellular aggregates such as spheroids 25 . Such high-resolution cell engineering is essential to replicate complex and highly ordered tissues in vivo because obtaining such tissues by current methods, including bioprinting, is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, we presented an easily reconfigurable method for particle separation in surface wave microfluidic devices increasing the performance of acoustic sorting techniques that are based on the frequency difference between two transducers. 9 Bidirectional sorting has been demonstrated by adjusting the inflow rates and electrical signal of transducers. The separation distance achieved with this method is half the wavelength, which is double that of conventional time-of-flight methods.…”
Section: -3mentioning
confidence: 99%
“…8 Recently, a continuously frequency modulated acoustic field method was applied in a surface acoustic wave (SAW) device. 9 However, in this technique, the particle movement is fluctuating, demonstrating limited selectivity (2.5-fold or greater diameter ratio) and efficiency (up to 83%). We propose a modified method that increases both selectivity and efficiency to open up a wide range of applications in biomedical engineering and beyond.…”
mentioning
confidence: 99%
“…The rapid separation and purification of biological particles have attracted considerable research attention recently due to their value in research, especially in medical diagnosis and environmental detection applications [ 1 , 2 , 3 ]. Centrifugation [ 4 , 5 ] is the most frequently used technology for separating biological particles.…”
Section: Introductionmentioning
confidence: 99%